Post firing reduction method: an innovation for standardized Raku glaze effect / Adibah Ali - Ali, Adibah (2016)
Raku has progressed gloriously over these years influencing many potters through its traditional and conventional firing methods. Raku is significant in a way which involves simplicity, spontaneity that we can say is endless. Raku is an essence of ceramic that presents a laid back firing method that produces variety of unexpected effects that will surprise due to the simplest firing method that the firing it was conducted. It had lead the researcher to modify the firing methods from producing spontaneous glaze effect to obtaining a planned glaze effect, and achieving a standardized one. This research involves a range of ceramic process including Raku kiln, glazing and firing experiments. Intended for this research, a Raku kiln was built to cater glaze firing experiments for small test pieces. Raku conventional reduction methods were innovated to obtain a reduction atmosphere that would be able to alter the glaze to a standardized effect for all test pieces. The main issue of Raku is the random glaze effect produced from it reduction methods. This issue has been made as this research's motivation due to the realized potential of Raku that was suitable for this research. 10 experiments were conducted for this research using 2 Raku kilns to acquire the required glaze effect hence the proper reduction atmosphere that would be the foundation of the glaze effect transformation. The reduction atmosphere was created through an innovative post firing reduction method of inserting combustible material into the kiln and the kiln was sealed while producing smoke. The smoke appearance during reduction process was the main factor that could modify the glaze effect if all the involving factors such as the firing temperature, amount of combustible material used and the reduction temperature atmosphere are a suitable combination. Therefore this research gives us anticipation that through an altered method of post firing reduction, we can achieve a planned standardized effect for Raku glaze.